2016
DOI: 10.1016/j.jcv.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and etiology of influenza-like-illness in households in Vietnam; it’s not all about the kids!

Abstract: HighlightsRhino, Influenza and Corona viruses caused ∼50% of ILI in Vietnam households.There was no clear seasonality for ILI, or for individual viruses causing ILI.Children did not contribute substantially to ILI burden or transmission.Seasonality and the contribution of children were unlike temporal settings.Seasonality and social factors may affect the involvement of children in ILI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
18
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
11
18
1
1
Order By: Relevance
“…Also, detection of the types of viruses and their relative frequency was similar to previous reports. The most common non‐influenza respiratory virus we detected was entero‐rhinovirus, consistent with other studies . In our study, the ratio of attack rates for vitamin D to placebo for entero‐rhinovirus, 0.83, represented the median effect for non‐influenza respiratory viruses, which ranged from 0.47 for human metapneumovirus to 1.17 for parainfluenza viruses 1‐3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, detection of the types of viruses and their relative frequency was similar to previous reports. The most common non‐influenza respiratory virus we detected was entero‐rhinovirus, consistent with other studies . In our study, the ratio of attack rates for vitamin D to placebo for entero‐rhinovirus, 0.83, represented the median effect for non‐influenza respiratory viruses, which ranged from 0.47 for human metapneumovirus to 1.17 for parainfluenza viruses 1‐3.…”
Section: Discussionsupporting
confidence: 90%
“…This was based on adherence to testing, and we reasoned that an increase in the number of swabs would make up for any reduction in sensitivity. The attack rate for all respiratory viruses in our study was 35%, which is comparable to other studies that have used RT‐PCR to detect infection in children . A study in the same population in Vietnam reported similar attack rates as ours .…”
Section: Discussionsupporting
confidence: 88%
“…There are only few studies that have investigated non‐influenza respiratory viruses in SARI patients of Vietnam or in the South‐East Asia region . Some studies have examined non‐influenza viruses in select patient populations such as children, refugees, or hospitalized and non‐hospitalized patients with respiratory disease . Gaps still exist, however, in understanding which viruses cause SARI in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Human rhinovirus (HRV) is the predominant cause of upper respiratory tract infections (URTIs) referred to as the common cold 14 . The virus has also been associated with lower respiratory tract illnesses, including exacerbation of asthma and chronic obstructive pulmonary disease 5, 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In household studies, family members experience rapid rates of reinfection (for instance, up to 5 infections in adults or 12 infections in young children per year) where each infection tends to be caused by a different HRV-type and rarely with the same HRV-type 4, 16, 17 . At a population level of observation, repeated reinfections in individuals appears to reflect the introduction and circulation of new types in the community, rather than persistence of the same HRV types 1821 .…”
Section: Introductionmentioning
confidence: 99%